Novel protective role for MAP kinase phosphatase 2 in inflammatory arthritis. Issue 1 (11th January 2019) - Schroeder, Juliane; Ross, Kirsty; McIntosh, Kathryn; Jabber, Shilan; Woods, Stuart; Crowe, Jenny; Patterson Kane, Janet; Alexander, James; Lawrence, Catherine; Plevin, Robin
Abstract : Objectives: We have previously shown mitogen-activated protein kinase phosphatase 2 (MKP-2) to be a key regulator of proinflammatory cytokines in macrophages. In the study presented here, we investigated the role of MKP-2 in inflammatory arthritis with a particular focus on neutrophils. Methods: To achieve this, we subjected MKP-2 deficient and wild type mice to collagen antibody induced arthritis, an innate model of arthritis, and determined disease pathology. To further our investigation, we depleted neutrophils in a prophylactic and therapeutic fashion. Last, we used chemotaxis assays to analyse the impact of MKP-2 deletion on neutrophil migration. Results: MKP-2 -/- mice showed a significant increase in disease pathology linked to elevated levels of proarthritic cytokines and chemokines TNF-α, IL-6 and MCP-1 in comparison to wild type controls. This phenotype is prevented or abolished after administration of neutrophil depleting antibody prior or after onset of disease, respectively. While MCP-1 levels were not affected, neutrophil depletion diminished TNF-α and reduced IL-6, thus linking these cytokines to neutrophils. In vivo imaging showed that MKP-2 -/- mice had an increased influx of neutrophils into affected joints, which was higher and potentially prolonged than in wild type animals. Furthermore, using chemotaxis assays we revealed that MKP-2 deficient neutrophils migrate faster towards a Leukotriene B4 gradient. This process correlated with a reduced phosphorylation of ERK in MKP-2 -/- neutrophils. Conclusions: This is the first study to show a protective role for MKP-2 in inflammatory arthritis.